2018
DOI: 10.1038/s41598-018-20878-0
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled clinical trial on bleaching sensitivity and whitening efficacy of hydrogen peroxide versus combinations of hydrogen peroxide and ozone

Abstract: The clinical efficacy regarding bleaching sensitivity and tooth shade lightening using a standard hydrogen peroxide (H2O2) bleaching gel was compared with the additional use of ozone either before or after application of H2O2. Using computer-generated tables, 45 participants were randomly allocated into three groups (n = 15 each) in this investigator-driven, single-centre trial. In Group 1, upper anterior teeth were bleached using ozone (produced via a healOzone X4 device) for 60 seconds, then 38% H2O2 for 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 42 publications
(72 reference statements)
5
50
0
7
Order By: Relevance
“…74 It has shown that the whitening efficacy of hydrogen peroxide is enhanced with application of ozone, without an increase of tooth hypersensitivity. 82 The same happens when nitrogen-doped titanium dioxide is combined with low concentrations of oxidant agents. 83 Other compounds like strontium chloride and potassium nitrate combined with fluoride do not interfere with the whitening effect, but they improve the process reducing the morphological changes in the enamel.…”
Section: General Classification Subgroups Examplesmentioning
confidence: 99%
See 1 more Smart Citation
“…74 It has shown that the whitening efficacy of hydrogen peroxide is enhanced with application of ozone, without an increase of tooth hypersensitivity. 82 The same happens when nitrogen-doped titanium dioxide is combined with low concentrations of oxidant agents. 83 Other compounds like strontium chloride and potassium nitrate combined with fluoride do not interfere with the whitening effect, but they improve the process reducing the morphological changes in the enamel.…”
Section: General Classification Subgroups Examplesmentioning
confidence: 99%
“…Besides, these kinds of dentifrices have potential activity against Streptococcus mutants . It has shown that the whitening efficacy of hydrogen peroxide is enhanced with application of ozone, without an increase of tooth hypersensitivity . The same happens when nitrogen‐doped titanium dioxide is combined with low concentrations of oxidant agents .…”
Section: Whitening Systemsmentioning
confidence: 99%
“…Antimicrobial activity was tested also tested on less studied bacterial species [21,22,23]. Another interesting application of ozonated water is the use at a cosmetic level for dental bleaching.…”
Section: Resultsmentioning
confidence: 99%
“…Concentração não descrita. Aplicação de ozônio para cada dente foi realizado duas vezes, nos dias 3 e 8, após o tratamento periodontal Al-Omiri et al, Jordânia (2018) 33 Avaliar a eficácia clínica em relação à sensibilidade ao clareamento usando um gel clareador padrão de peróxido de hidrogênio (H2O2) comparada com o uso adicional de ozônio antes ou após a aplicação desse peróxido.…”
Section: Autor/ País/ Anounclassified